Adipose tissue‐derived stem cells inhibit hypertrophic scar (HS) fibrosis via p38/MAPK pathway. Issue 3 (27th September 2018) - Chai, Chi‐Yung; Song, Junlong; Tan, Zhenwei; Tai, I‐Chun; Zhang, Chaoying; Sun, Shengrong
Abstract: Objective: The current study was designed to investigate the effects and underlying mechanisms of adipose tissue‐derived stem cells (ADSCs) on hypertrophic scar (HS) fibrosis. Method: Real‐time quantitative polymerase chain reaction (qRT‐PCR) and Western blot analysis were performed to detect the expression of collagen I (Col1), collagen III (Col3), and α‐smooth muscle actin (α‐SMA) after fibroblasts and cultured HS tissues were treated with ADSC medium. All data were analyzed by using SPSS17.0 software. Statistical analysis was performed by Student t tests. Results: The in vitro study showed that ADSC medium decreased the expression of Col1, Col3, and α‐SMA. In addition, the protein level of p‐p38 was downregulated by ADSC medium treatment in a concentration dependent manner. Conclusion: The current study demonstrated that ADSC could decrease collagen deposition and scar formation in in vitro experiments. The regulation of the p38/MAPK signaling pathway might play an important role in the process.